Position, Elevation, Ice Thickness and Bedrock Elevation of Stations along the Routes in East Queen Maud Land and Enderby Land, East Antarctica - WATANABE, Okitsugu; FUJII, Yoshiyuki; NISHIO, Fumihiko; MOTOYAMA, Hideaki (National Institute of Polar Research, 1992)
P(論文) departmental bulletin paper